Insights Into the Molecular Mechanisms of Late Flowering in Prunus sibirica by Whole-Genome and Transcriptome Analyses - Wanyu Xu; Wanyu Xu; Wanyu Xu; Wenquan Bao; Huimin Liu; Huimin Liu; Huimin Liu; Chen Chen; Chen Chen; Chen Chen; Haikun Bai; Haikun Bai; et al. (Frontiers in Plant Science, 2022)
Freezing during the flowering of Prunus sibirica is detrimental to fruit production. The late flowering (LF) type, which is delayed by 7–15 days compared with the normal flowering (NF) type, avoids damages at low temperature, but the molecular mechanism of LF remains unclear. Therefore, this study was conducted to comprehensively characterize floral bud differentiation. A histological analysis showed that initial floral bud differentiation was delayed in the LF type compared to the NF type. Genome-wide associated studies (GWAS) showed that a candidate gene (PaF106G0600023738.01) was significantly associated with LF type. It was identified as trehalose-6-phosphate phosphatase (PsTPPF), which is involved in trehalose-6-phosphate (Tre6P) signaling pathway and acts on floral transition. A whole-transcriptome RNA sequencing analysis was conducted, and a total of 6,110 differential expression (DE) mRNAs, 1,351 DE lncRNAs, and 148 DE miRNAs were identified. In addition, 24 DE mRNAs related with floral transition were predicted, and these involved the following: three interactions between DE lncRNAs and DE mRNAs of photoperiod pathway with two mRNAs (COP1, PaF106G0400018289.01 and CO3, MXLOC_025744) and three lncRNAs (CCLR, LTCONS_00031803, COCLR1, LTCONS_00046726, and COCLR2, LTCONS_00046731); one interaction between DE miRNAs and DE mRNAs with one mRNA, encoding trehalose-6-phosphate synthase (PsTPS1, PaF106G0100001132.01), and one miRNA (miRNA167h). Combined with the expression profiles and Tre6P levels, functions of PsTPPF and PsTPS1 in Tre6P regulation were considered to be associated with flowering time. A new network of ceRNAs correlated with LF was constructed, and it consisted of one mRNA (PsTPS1), one lncRNA (TCLR, LTCONS_00034157), and one miRNA (miR167h). This study provided insight into the molecular regulatory mechanism of LF in Prunus sibirica.